Lentilactobacillus kefiri SGL 13 and Andrographis paniculata alleviate dextran sulfate sodium induced colitis in mice - Manna, Laura; Rizzi, Eleonora; Bafile, Eleonora; Cappelleri, Andrea; Ruscica, Massimiliano; Macchi, Chiara; Podaliri Vulpiani, Michele; Salini, Romolo; Rossi, Emanuela; Panebianco, Concetta; Perri, Francesco; Pazienza, Valerio; et al. (Frontiers in Nutrition, 2023)
Inflammatory bowel diseases (IBD) are chronic inflammatory conditions that typically involve diarrhea, abdominal pain, fatigue, and weight loss, with a dramatic impact on patients’ quality of life. Standard medications are often associated with adverse side effects. Thus, alternative treatments such as probiotics are of great interest. The purpose of the present study was to evaluate the effects of oral administration of Lentilactobacillus kefiri (basonym: Lactobacillus kefiri) SGL 13 and Andrographis paniculata, namely, Paniculin 13™, on dextran sodium sulfate (DSS)-treated C57BL/6J mice. Colitis was induced by administering 1.5% DSS in drinking water for 9 days. Forty male mice were divided into four groups, receiving PBS (control), 1.5% DSS, Paniculin13™ and 1.5% DSS + Paniculin 13™. The results showed that body weight loss and Disease Activity Index (DAI) score were improved by Paniculin 13™. Moreover, Paniculin 13™ ameliorated DSS-induced dysbiosis, by modulating the gut microbiota composition. The gene expression of MPO, TNFα and iNOS in colon tissue was reduced and these data matched with the histological results, supporting the efficacy of Paniculin 13™ in reducing the inflammatory response. No adverse effects were associated to Paniculin 13™ administration. In conclusion, Paniculin 13™ could be an effective add-on approach to conventional therapies for IBD.